2022
DOI: 10.1155/2022/5475832
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Circulating Exosomes Promote Protection of the Pulmonary Endothelial Barrier by Inhibiting EndMT and Oxidative Stress through Down-Regulation of the TGF-β Pathway: A Potential Explanation for the Obesity Paradox in ARDS

Abstract: The “obesity paradox in acute respiratory distress syndrome” (ARDS) refers to the phenomenon in which obesity is associated with higher morbidity but lower mortality in patients with ARDS. Endothelial-to-mesenchymal transition (EndMT) represents a key link in the interaction between endothelial disruption and mesenchymal fibrosis under inflammatory and oxidative conditions, which represent the intersectional pathophysiology of ARDS. Adipose tissue is considered to constitute the major source of circulating exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The particle size distribution of hiPSC-exosomes was measured by nanoparticle tracking analysis (Particle Metrix zataview, Germany). Marker proteins of hiPSC-exosomes were detected by western blotting using anti-CD9 (Yang et al, 2022) (Affinity, DF6565), anti-TSG101 (Qi et al, 2022) (Proteintech, 67381-1-Ig), and negative protein marker anti-Calnexin (Sun et al, 2021a) (Proteintech, 66903-1-Ig) antibodies. hiPSC-exosome-specific protein markers CD63 (BD, 556019) and CD81 (BD, 551108) were detected by a Flow NanoAnalyzer (Nanofcm, China).…”
Section: Characterization Of Hipsc-exosomesmentioning
confidence: 99%
“…The particle size distribution of hiPSC-exosomes was measured by nanoparticle tracking analysis (Particle Metrix zataview, Germany). Marker proteins of hiPSC-exosomes were detected by western blotting using anti-CD9 (Yang et al, 2022) (Affinity, DF6565), anti-TSG101 (Qi et al, 2022) (Proteintech, 67381-1-Ig), and negative protein marker anti-Calnexin (Sun et al, 2021a) (Proteintech, 66903-1-Ig) antibodies. hiPSC-exosome-specific protein markers CD63 (BD, 556019) and CD81 (BD, 551108) were detected by a Flow NanoAnalyzer (Nanofcm, China).…”
Section: Characterization Of Hipsc-exosomesmentioning
confidence: 99%
“…Further, Qi et al 41 found that adipose-derived exosomes, a type of extracellular vesicle, were protective against endothelial barrier disruption by downregulating the TGF-β pathway. 41 Additionally, some investigators argue that obesity mitigates ventilator-induced lung injury by impeding chest wall expansion and reducing transpulmonary airway pressure. Obesity has a significant effect on suppressing circulating levels of natriuretic peptides.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 Obese patients with ALI have also shown lower levels of pro‐inflammatory cytokines, such as interleukin‐6 (IL‐6) and −8 (IL‐8), 40 which may play a role in protection against severe outcomes by attenuating cytokine storms. Further, Qi et al 41 found that adipose‐derived exosomes, a type of extracellular vesicle, were protective against endothelial barrier disruption by downregulating the TGF‐β pathway. 41 Additionally, some investigators argue that obesity mitigates ventilator‐induced lung injury by impeding chest wall expansion and reducing transpulmonary airway pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Qi et al [ 110 ] found that the exosomal miRNAs from the adipose tissue are essential for the TGF-β1-mediated pulmonary fibrosis. The level of circulating exosomal miR-122-5p was significantly higher in obese ARDS mice than lean ARDS mice.…”
Section: Factors Involved With the Explanation Of Obesity Paradox In ...mentioning
confidence: 99%